MANAJEMEN SEKOLAH YANG EFEKTIF DI SEKOLAH ISLAM BURAPHA WITTAYA NARATHIWAT THAILAND SELATAN - Nurdin Likia; Gilang Aulia Prasetya; Hasyim Asy’ari (Smart Education, 2025)
Abstract: Educational institutions can be effective schools. One of them is a school with leaders and work teams who consider and respond intelligently to factors within the school. In this era of change and modern times, many creative and innovative ideas are emerging for modern schools with various names such as high schools, comprehensive schools, model schools, and so on. Several developed countries call this movement effective schooling. The author believes it is important to discuss effective school management. This is because not many schools are able to manage their schools effectively, so there are still many educational institutions that fail to achieve their stated goals. An effective school is a school that achieves the goals it sets. In this research, we focus on effective school management from the perspective of principals' efforts to create effective schools, using qualitative research methods. I hope that writing this article can help schools think about effective school management in order to improve the quality of school learning that satisfies all parties involved. Based on the results of interviews with the principal and teachers of Burapha Wittaya Islamic School who have succeeded in implementing effective school management so that this school is able to produce good quality graduates even though this school is in a special area and there are several obstacles in effective school management, but this school is able to overcome these obstacles. that happened.Keywords: Management, Management, Effective Schools, Islam. Abstrak: Institusi pendidikan bisa menjadi sekolah yang efektif. Salah satunya adalah sekolah dengan pemimpin dan tim kerja yang mempertimbangkan dan merespons secara cerdas faktor-faktor di dalam sekolah. Di era perubahan dan zaman modern ini, banyak bermunculan ide-ide kreatif dan inovatif untuk sekolah modern dengan berbagai nama seperti sekolah menengah atas, sekolah komprehensif, sekolah teladan, dan lain sebagainya. Beberapa negara maju menyebut gerakan ini sebagai sekolah efektif. Penulis berpendapat penting untuk membahas manajemen sekolah yang efektif. Hal ini disebabkan karena tidak banyak sekolah yang mampu mengelola sekolahnya secara efektif, sehingga masih banyak lembaga pendidikan yang gagal mencapai tujuan yang telah ditetapkan. Sekolah yang efektif adalah sekolah yang mencapai tujuan yang ditetapkannya. Dalam penelitian ini, kami fokus pada manajemen sekolah yang efektif dari sudut pandang upaya kepala sekolah untuk menciptakan sekolah yang efektif, dengan menggunakan metode penelitian kualitatif. Saya berharap dengan menulis artikel ini dapat membantu sekolah memikirkan manajemen sekolah yang efektif guna meningkatkan kualitas pembelajaran sekolah yang memuaskan semua pihak yang terlibat. Berdasarkan hasil wawancara kepala sekplah dan guru Sekolah Islam Burapha Wittaya yang telah berhasil dalam menerapkan manajemen sekolah yang efektif sehingga sekolah ini mampu menghasilkan mutu lulusan yang baik walaupun sekolah ini berada di daerah khusus dan terdapat beberapa kendala dalam pengeloaan sekolah efektif namun sekolah ini mampu mengatasi kendala yang terjadi.Kata Kunci: Manajemen, Pengeloaan, Sekolah Efektif, Islam